Şehitlik Dergâhı Tarihçesine Bir Katkı: Abdünnâfi Baba'nın Ahmed İsmet Efendi'ye Verdiği İcâzetnâme - (:unkn) unknown (My University, 2015)
Rumelihisarı Şehitlik Dergâhı İstanbul'un en eski tarîkat merkezlerinden biridir. Dergâhın kurucusu ve erken dönem tarihinin bilinen ismi Hacı Bayrâm-ı Velî'nin halifelerinden Bedreddin Efendi'dir. Bedreddin Efendi'nin soyundan gelenler tarafından faaliyetlerini sürdüren dergâh, asıl ününe Abdünnâfi Baba'nın postnişinliği zamanında kavuşmuş ve sonrasında onun adı ile anılır olmuştur. Bu makalede Abdünnâfi Baba'nın 1325/1908 tarihinde ulemâdan Ahmet İsmet Efendi'ye verdiği icâzetnâme değerlendirilecek, dergâhın etkili olduğu çevreler ve geliştirdiği ilişkiler bu icâzetnâme bağlamında ortaya konulmaya çalışılacak, Osmanlı İstanbul'undaki tarîkat çevrelerinin ve Şehitlik Dergâhı'nın tarihine ilişkin daha önce incelenmemiş bir belge ele alınarak ilgili literatüre katkı sunulacaktır.

Rumelihisarı Şehitlik Lodge is among the oldest Sufi convents in Istanbul. It was established by Bedreddin Efendi, who was a disciple of Hacı Bayram-i Veli. The available sources provide some significant information about Bedreddin Efendi as a prominent figure in the historiography of the convent. The lodge continued its activities under the supervision of Bedreddin Efendi's lineage, yet became famous during the mastership of Abdünnafi Baba . From then on the lodge has been known Nafi Baba lodge. In this essay we will analyze the diploma granted by Abdünnafi Baba to Ahmet İsmet Efendi, a member of the ulama class in 1325/1908 and in this manner we will shed light to the circles influnced by the lodge community as well as their relationships through the lense of the document. In doing this, we will make a humble contribution to the relevant literature on the history of Ottoman Sufi circles and Şehitlik Lodge by analyzing this new and significant document.
A Contribution to the Historiography of Şehitlik Lodge: the Diploma (ijazetname) granted by Abdünn?fi Baba to İsmet Efendi
Keywords: Din Bilimi